Association of TLR2 and TLR4 Gene Single Nucleotide Polymorphisms with Fungal Keratitis in Chinese Han Population. (January 2014) - Wang, N.; Zhao, G.Q.; Gao, A.; Che, C.Y.; Qu, X.L.; Liu, Y.; Guo, Y.L.
Abstract Purpose: Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) play a crucial role in the primary defense against fungal pathogens, and since genetic variation in genes may regulate the response. This study aimed to test whether variants in the TLR4 gene are associated with fungal keratitis (FK) of Chinese Han population. Materials and methods: Two-hundred sixty-nine subjects (109 cases and 160 matched controls) in a Han Chinese population were genotyped. Seven single nucleotide polymorphisms (SNPs) which located, respectively, in the TLR2 and TLR4 genes were selected and their associations with FK risk factors were assessed. Results: Allele A of TLR4 rs10983755 was found significantly higher in the group of FK patients, being detected in 32.11% of the FK patients alleles and in 22.19% of the healthy control alleles (p = 0.01).Those AA/AG genotypes carrying the allele A of rs10983755 had a risk effect on the etiology of FK, and the odds ratio for the FK patients versus controls was 2.075 (OR = 2.075, 95%CI = 1.264–3.407). The Ht3 haplotype, which carried the A allele of TLR4 rs10983755, was associated with the significantly increased risk of FK (OR = 1.786, 95%CI = 1.207–2.642). While, the Ht2 haplotype, which carried the wild G allele of TLR4 rs10983755, was a protective haplotype (OR = 0.488, 95%CI = 0.333–0.715). The genotype and allele frequency of TLR2 showed no differences between the two groups (p > 0.05). Conclusions: The rs10983755, located in the 5′-untranslated region (UTR) of TLR4, was most strongly associated with FK of Chinese Han population (p < 0.05). The analysis of TLR2 gene polymorphisms showed no significant association upon FK susceptibilities of Chinese Han population.